Adverse pregnancy and perinatal outcome in patients with recurrent pregnancy loss: Multiple imputation analyses with propensity score adjustment applied to a large‐scale birth cohort of the Japan Environment and Children's Study. (13th December 2018) - Sugiura‐Ogasawara, Mayumi; Ebara, Takeshi; Yamada, Yasuyuki; Shoji, Naoto; Matsuki, Taro; Kano, Hirohisa; Kurihara, Takahiro; Omori, Toyonori; Tomizawa, Motohiro; Miyata, Maiko; Kamijima, Michihiro; Saitoh, Shinji; et al.
Abstract : Problem: Several studies have reported the increased risk of preterm birth, premature rupture of membranes, and low birth weight in patients with recurrent pregnancy loss (RPL). There have been a limited number of large population‐based studies examining adverse pregnancy and perinatal outcome after RPL. Multiple‐imputed analyses (MIA) adjusting for biases due to missing data is also lacking. Method of study: A nationwide birth cohort study known as the "Japan Environment and Children's Study (JECS)" was conducted by the Ministry of the Environment. The subjects consisted of 104 102 registered children (including fetuses or embryos). Results: No increased risk of a congenital anomaly, aneuploidy, neonatal asphyxia, or a small for date infant was observed among the children from women with a history of RPL. A novel increased risk of placental adhesion and uterine infection was found. The adjusted ORs using MIA in women with three or more PL were 1.76 (95% CI, 1.04‐2.96) for a stillbirth, 1.68 (1.12‐2.52) for a pregnancy loss, 2.53 (1.17‐5.47) for placental adhesion, 1.87 (1.37‐2.55) and 1.60 (.99‐2.57) for mild and severe hypertensive disorders of pregnancy, respectively, 1.94 (1.06‐3.55) for uterine infection, 1.28 (1.11‐1.47) for caesarean section and .86 (.76‐.98) for a male infant. Conclusion: MIA better quantified the risk, which could encourage women who might hesitate to attempt a subsequent pregnancy.